Effect of dapagliflozin in patients with heart failure on reducing cardiovascular mortality in federal project on the prevention of cardiovascular diseases - M. V. Zhuravleva; S. N. Tereshchenko; I. V. Zhirov; S. V. Villevalde; T. V. Marin; Yu. V. Gagarina (Российский кардиологический журнал)
Aim. To assess the effect of dapagliflozin in patients with heart failure with reduced ejection fraction (HFrEF) on reducing cardiovascular mortality as the main goal of a federal project on the prevention of cardiovascular diseases.Material and methods. All adult Russian patients with a documented NYHA class II-IV HFrEF (EF £40%) were considered the target population. The characteristics of the patients corresponded to those of the Russian Hospital Heart Failure Registry (RUS-HFR). The study looked at an increase in the dapagliflozin use in addition to standard therapy by 10% of patients annually in 2021-2023 and calculated the number of deaths that could be prevented. Cardiovascular mortality curve was created by extrapolation of the DAPA-HF study results using the Kaplan-Meier method. Further, the contribution of prevented deaths with dapagliflozin to the achievement of regional and federal targets for reducing cardiovascular mortality was calculated for 1, 2, and 3 years. Results. In case of 10% annual increase in dapagliflozin use in patients with NYHA class II-IV HFrEF, this will allow:—   to prevent an additional 1,736 cardiovascular deaths in the first year, achieving the target of federal project on the prevention of cardiovascular diseases in 2021 by 5,9%;—   to prevent an additional 3,784 cardiovascular deaths in the second year, achieving the target of federal project on the prevention of cardiovascular diseases in 2022 by 12,9%;—   to prevent an additional 5,485 cardiovascular deaths in the third year, achieving the target of federal project on the prevention of cardiovascular diseases in 2023 by 18,7%.Conclusion. The use of dapagliflozin in patients with HFrEF will reduce mortality from cardiovascular diseases.